From poetic fragments to a story: healing a traumatic rupture by re-assembling a fractured poem - Simchon, Michal (Journal of poetry therapy, 2025)
Survivors of trauma, whose life stories have been disrupted, can be helped through processes of reading and writing to regain emotional stability, recreate their identity and go on with their lives. This article proposes combining poetry therapy with narrative therapy as a treatment option for people who have endured trauma, which can sometimes leave individuals frozen and mute. Poetry can put the inexpressible into words, and thus allow the individual to begin telling his or her story and to find meaning in what has occurred. This paper describes a poetry–narrative treatment approach that takes advantage of the unique literary and structural qualities of a poem and mobilizes them, through a process of writing, to enable healing. The person is thus helped to turn the fragments of his or her life into a story with meaning and significance. The article includes a case study to demonstrate the proposed method.